(untitled) (Nucleus, 2011)
With current incentives to search for sources of renewable energy, the culture of crambe (Crambe abyssinica) before, basically, to forage production, has been widely cultivated in order to produce vegetable oil. However crop science information for this culture still prove to be scarce in the scientific community. However, due to be culture that has taken new directions lately, and it presents a promising potential for the production of vegetable oils, studies with greater demand for commitment, are studies related to seed quality, aiming at the sustainable planting. The aim of this study was to evaluate the effects of light on seed germination of Crambe abyssinica. The statistical design used in the experiment was a completely randomized design with 2 treatments (absence or presence of light) and ten repetitions, totaling 20 experimental units. It is concluded that light is on promoting factor positive changes in seed germination of crambe. In the presence of light seeds of crambe showed higher percentages of normal seedlings and dry mass. Crambe seed was classified as neutral photoblastic.